برنامج مقترح للحد من صعوبات التعلم في الرياضيات في ضوء نظرية جاردنر - لطيف متولي, فكري (Sciences de l'Homme et de la Société; Vol. 11 (2014): SCIENCES DE L'HOMME ET DE LA SOCIÉTÉ)
يتمثل هدف البحث الرئيس في التعرف على أثر برنامج مقترح للحد من صعوبات التعلم في الرياضيات في ضوء نظرية جاردنر كإحدى نظريات التكوين العقلي. ويتناول أحد الاضطرابات الاكاديمية حيث يتسم الأطفال الذين يعانون من هذا الاضطرابات بالقصور في العديد من مجالات الحياة عامة والصعوبات الاكاديمية خاصة، وذلك في مرحلة من أهم مراحل النمو الإنساني . يستخدم البحث المنهج شبه التجريبي مع أفراد العينة. وتشتمل عينة البحث على (5) أطفال من ذوي صعوبات التعلم في الرياضيات. وقد استخدم البحث برنامج مقترح لأطفال ذوي صعوبات تعلم في الرياضيات واختبار تشخيص لصعوبات التعلم في الرياضيات.    The main objective of this research is to identify the impact of a proposed program to reduce learning difficulties in mathematics in the light of the theory as one of Gardner's theories of mental training. One deals with disorders characterized by Academy where children who suffer from this disorder deficient in many areas of life, public and private, and academic difficulties in the phase of the most important stages of human development. Find used quasi-experimental approach with the sample. And include a sample search on (5) of the children with learning difficulties in mathematics. And use the Find a proposed program for children with learning difficulties in mathematics and a diagnostic test for learning difficulties in mathematics.